Fat Leonard : how one man bribed, bilked, and seduced the U.S. Navy - Whitlock, Craig (Simon & Schuster, 2024)
"All the admirals in the US Navy knew Leonard Glenn Francis--either personally or by his legendary reputation. He was the larger-than-life defense contractor who greeted them on the pier whenever they visited ports in Asia, ready to show them a good time after weeks at sea while his company resupplied their ships and submarines. He was famed throughout the fleet for the gluttonous parties he hosted for officers: $1,000-per-person dinners at Asia's swankiest restaurants, featuring unlimited Dom Pérignon, Cuban cigars, and sexy young women. On the surface, with his flawless American accent, he seemed like a true friend of the Navy. What the brass didn't realize, until far too late, was that Francis had seduced them by exploiting their entitlement and hubris. While he was bribing them with gifts, lavish meals, and booze-fueled orgies, he was making himself obscenely wealthy by bilking American taxpayers. Worse, he was stealing military secrets from under the admirals' noses and compromising national security. Based on reams of confidential documents--including the blackmail files that Francis kept on Navy officers--Fat Leonard is the full, unvarnished story of a world-class con man and a captivating testament to the corrosive influence of greed within the ranks of the American military."--